Studi Metode Smooth Particle Hydrodynamics Pada Fluida - Hafid Setyo Hadi (Techno Bahari, 2018)
Fluids, a phenomenon that is difficult to be modeled realisticly, can be done by a mathematical approach. This research is interesting in the fluid simulation by applying a fast and stable particel model. Fluids flow is simulated in the boundaries of geometry space. The research is focused on simulations where mathematical equations and fluid dynamics are needed to define complex fluid movements. Simulations made in rendering mode: points ot dots and to display collision interactions between fluid particles and the dividing wall. The Smooth Particle Hydrodynamic (SPH) method with the Lagrange equation will be applied in this analysis.